1963
DOI: 10.1037/h0045868
|View full text |Cite
|
Sign up to set email alerts
|

The ratio theory of intermediate size discrimination.

Abstract: A theory based on Kelson's adaptation level formulation was presented that was capable of integrating the data on the problem of transposition of intermediate size. These data were analyzed and new research reported that revealed several phenomena of importance for any theory of intermediate size discrimination. The modes of response either replicated or reported were transposition, systematic preference for the absolute stimulus, neither absolute nor relational choice, equal preference for 1 test stimuli, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

1964
1964
1989
1989

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…A recent review of the literature (Zeiler, 1963) revealed that species other than pigeons transposed when the training and the test sets were similar to each other. With the extinction series, the current findings were that pigeons transferred absolutely whether or not the training and the test sets were very similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of the literature (Zeiler, 1963) revealed that species other than pigeons transposed when the training and the test sets were similar to each other. With the extinction series, the current findings were that pigeons transferred absolutely whether or not the training and the test sets were very similar.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption is that stimulus preference in the test is controlled by the nature of the effective stimulus in the original discrimination. This may be the middle-size relationship, the absolute physical size of the SD, or some contextually determined property (Zeiler, 1963). Since the stimulus responded to in the test would differ depending on which of these properties controlled the discriminative behavior, the essential nature of the stimulus is identified by the test element chosen.…”
mentioning
confidence: 99%
“…(For theoretical analyses, see Goldstein, Krantz, & Rains, 1965;Spence, 1942;Zeiler, 1963aZeiler, , 1963bZeiler, , 1964.) Each of these theories assumes (a) Ss are alike with respect to the stimulus property used as a cue, and (b) no S has more than one basis for responding; but these assumptions appear doubtful for human Ss.…”
mentioning
confidence: 99%
“…While young children transpose with test sets one step removed from the training set and show first absolute and then random response as the test inc reases in distance from the training set (Zeiler, 1963) and somewhat older children display relational transfer at all distances (Kuenne, 1946), a recent study with adults (Zeiler, 1964) revealed quite different effects.…”
Section: Problemmentioning
confidence: 99%